Additions to the scorpion fauna of Panama and Costa Rica - Lourenco, Wilson R (Revista de Biología Tropical, 1996)
Two new additions to the scorpion fauna of Panama and Costa Rica are described: the male of Chactas bonito Francke and Stockwell, 1987, Chactidae, a species preYiously described from Costa Rica but based only on female specimens, and Tityus mongei n.sp., Buthidae, from Colon Province in Panama. Tityus mongei is closely related to Tityus sastrei Lourenco and Florez, described from the Pacific coasta! region of Colombia. In comparison with T.sastrei , T. mongei is characterized by (1) lighter more yellow coloration (2) pedipalp keels more strongly crenulated (3) the subaculeous tooth is strong and yery stocky and (4) basal middle lamellae of pectines strongly dilated